Surface group representations with maximal Toledo invariant - Burger, Marc; Iozzi, Alessandra; Wienhard, Anna (Comptes rendus mathematique, 2003)
We study representations of compact surface groups on Hermitian symmetric spaces and characterize those with maximal Toledo invariant.